Influence of dietary isoleucine:lysine ratio on the optimal tryptophan:lysine ratio for 13- to 24-lb pigs - Nitikanchana, S.; Chipman, A.L.; Usry, J.; Patience, J.F.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 475 nursery pigs (initially 13.4 lb and 5 d postweaning) were used to determine the influence of the standardized ileal digestible (SID) isoleucine:lysine ratio on the optimal SID tryptophan:lysine ratio for growth performance of nursery pigs. This experiment was conducted in the all-in, all-out nursery at the Swine Nutrition Farm at Iowa State University. Each treatment had 8 replications with 4 or 5 pigs per pen, with equal numbers of barrows and gilts within block and across treatments. Pens were allotted to 1 of 12 treatments in a randomized complete block design. Treatments were arranged as a 2 × 6 factorial with main effects of 2 SID isoleucine:lysine ratios (52 and 60% of lysine) and 6 SID tryptophan:lysine ratios (14.7, 16.6, 18.5, 20.4, 22.3, and 24.0% of lysine). Treatment diets were fed for 14 d, then a common diet was fed from d 14 to 21. Overall, no interactions (P > 0.27) were observed between SID isoleucine:lysine and SID tryptophan:lysine ratios. For the main effect of SID isoleucine:lysine ratio, no differences (P > 0.21) were observed in growth performance between pigs fed the 52 or 60% SID isoleucine:lysine ratio. Increasing the SID tryptophan:lysine ratio also had no effect (P > 0.30) on growth performance. In conclusion, dietary SID isoleucine:lysine ratio did not influence the response to increasing SID tryptophan:lysine ratios in 13- to 24-lb pigs. Our results also suggested that the SID isoleucine:lysine ratio is not greater than 52% for pigs fed diets that do not contain blood products. Further research is needed to determine the optimal tryptophan:lysine ratio for 13- to 24-lb pigs.
Keywords: Swine; Isoleucine; Nursery pig; Tryptophan